Investigating the Impact of Self-Efficacy on Elementary Students’ Mathematical Problem-Solving Skills - Adinda Wulan Fitriyah; Anisya Fitriani; Putri Melianti (MIREJ: Multidisciplinary Innovation Research Journal, 2026)
This study aims to investigate the relationship between academic self-efficacy and mathematical problem-solving among elementary school students in Cirebon, Indonesia. With the increasing recognition of psychological factors in 21st-century education, especially in primary education, there is a need for empirical validation to understand how self-efficacy operates at this developmental stage. A quantitative correlational approach was utilized, involving 50 students from five public elementary schools, chosen through purposive sampling. Data collection involved validated mathematical problem-solving assessments and academic self-efficacy questionnaires. The instruments demonstrated acceptable reliability (Cronbach's alpha > 0.6) and content validity was confirmed by experts in the field. Statistical analyses included tests for normality and homogeneity, Pearson correlation, and simple linear regression. While the data were not normally distributed, they satisfied the assumptions of homogeneity. The results indicated no significant relationship between academic self-efficacy and problem-solving ability (r = -0.014, p = 0.922), with regression analysis further confirming its negligible predictive power (β = -0.029, p = 0.922). These findings imply that academic self-efficacy may not be a crucial determinant of mathematical problem-solving performance at the elementary level, possibly due to the students’ limited metacognitive development. Theoretically, this study contributes to the field of educational psychology by challenging the universality of self-efficacy's influence in early education. Practically, it prompts educators and policymakers to consider developmental readiness when creating interventions designed to enhance self-belief. Future research should investigate mediating variables such as cognitive strategies, emotional regulation, and classroom environment to better understand academic performance among early learners.